Estudio sobre las estructuras de dominación en el sistema educativo capitalista ecuatoriano, a partir del análisis de las nociones de habitus y capital cultural propuestas por Pierre Bourdieu - Rodas Coloma, Alejandro (2024)
In this sludy, it is clear that the capitalist system of education has been historically built around a myth that self-proclaims itself as a supposed "democratic instrument of social mobility". However, Bourdieu's analysis shows that the real function of the capitalist educational system is to legitimize and ensure the reproduction of unequal opportunities. It changes the term "culture•, to the belief that such socially conditioned priVileges are a so-called "merit" or personal "gifts". The Bourdieano thinking allows us to reflect on the structural problems that society has, in particular, the imbalances begin to elucidate lrom lhe French context regarding education, The Ecuadorian society is not foreign to this dynamic as we have permitted this "Wester" style education, which ts eminenlly capítalist, to inlillrate ilsell among us. The habitus generales a system layout ol thoughts, perceptions, expressions and actions that are seemingly spontaneous; however, they reOect the internalized social history, in which the social, economic and cultural environment influenced their produclion conditions. Social classes are determined by these objective regularities that generate "reasonable" or "common sense" behaviors, which will build and slrengthen social, economic and cultural barriers that guarantee the "social reproduction". The "mass educalion", in a capttalist logic, has failed to eliminate the existing social barriers and provide ali indiVíduals the same opportunilies of access to educalion. Universal access to educalion in practica is referred to as utQpias which are detrimental to lhe different social sectors, reslrictions imposed by the state.